Meningkatkan Kemampuan Mengamati, Menanya, Mengolah, Menalar, Menyajikan, Menyimpulkan, dan Mencipta/ Mengkreasi melalui Metode Bercakap-Cakap pada Anak SD Islam Ar-Rosyid Kota Mojokerto - Ihwan, Muhammad (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2017)
Early childhood must be trained to dare to express the feel and in thinking, so that later on the child will not be shy, easy to express opinions in front of many people and easy to interact. In addition the importance of good speaking skills, will gain social benefits at the next age. Therefore speaking development, that is speaking should be developed optimally from an early age. Problems raised in this research are: 1) How does the activity of teacher and student in learning observing, asking, processing, reasoning, presenting, concluding, and creating / creating through the method of conversing in elementary school students Islam Islam Ar-Rosyid Mojokerto? 2) How does the student's response in learning observe, question, process, reason, present, summarize, and create / create through the method of conversation in children of Islamic Elementary School Ar-Rosyid Mojokerto? 3) Is the method of conversation able to improve the ability to observe, question, process, reason, present, summarize, and create / create in the children of Islamic Elementary School Ar-Rosyid Mojokerto? This research is a class action research (action research), because it is done to solve the problem of learning in class. The troubleshooting process is done in two cycles of each 1-time meeting cycle. The success indicator is scored ≥ 78 from the maximum score of at least 80% of the number of students. The result of data analysis shows that there is an increase of pre-research activity, cycle I and cycle II research, it proves that teacher activity has increased from pre cycle of 66.67% cycle 77.78% and Cycle II 88.89%, while children activity has increased from pre cycle 44.44 % cycle I 55.56% and Cycle II 88.89% and the response of children in improving the ability of observing, questioning, processing, reasoning, presenting, concluding, and creating / creating through the method of conversation increased from pre cycle 38.89% cycle I 77.78% and Cycle II 94.44%. By improving the ability to observe, question, process, create, present, summarize, and create / create through the method of conversation can be achieved maximally and proven in cycle II improving the ability to observe, question, process, reason, present, summarize and create / Creating through the method of conversation has increased significantly.